Pengaruh Fraksi Volume Filler terhadap Kekuatan Bending dan Ketangguhan Impak Komposit Nanosilika – Phenolic - Diharjo, Kuncoro; Elharomy, Ischiadica; Purwanto, Agus (Jurnal Rekayasa Mesin, 2014)
The objective of this research is to investigate the effect of filler volume fraction on bending strength and impact toughness of nanosilica-phenolic composites. The research materials used were nanosilika powder, LP-1Q-EX phenolic resin, MEXPO catalyst and P-EX promotor. In this research, the filler volume fraction of nanosilica were varied into 10-60%. The composites were produced by using a hand lay-up method. All specimens were post cured at 100˚C for 60 minutes. The specimens were conducted with universal testing machine and impact izod testing machine. The fracture surfaces of the specimens were observed by using scanning electron microscopy (SEM). This result showed that the addition of nanosilica increased the bending strength and impact toughness. The maximum bending strength and impact toughness occured on the specimens whose 30% of nanosilica (97,01 MPa and 8134,70 kJ/m ). SEM images showed better interaction of filler and matrix at 30% volume fraction of nanosilica.Keywords : composite, nanosilica, phenolic, bending, impact